2013
DOI: 10.1177/0961203313502861
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in systemic lupus erythematosus women one year after rituximab therapy

Abstract: The objective of this study was to assess the effects of rituximab on bone mineral density (BMD) in women with systemic lupus erythematosus (SLE) 1 year after treatment. Thirty active female SLE patients treated with rituximab were compared with 43 SLE women not treated with rituximab. BMD was measured using dual energy X-ray absorptiometry (DEXA) before initiating biologic therapy and after 1 year. The mean age was 38.5 ± 2.1 years; median disease duration was 7 years. In the rituximab group, after 1 year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
5
1
2
Order By: Relevance
“…This study describes the effect of anti-CD20 antibody treatment on bone mass in hematological patients as well as in mice. Despite previous studies suggesting that administration of anti-CD20 antibodies to SLE and RA patients may lead to bone loss (8,9), our data, albeit in a limited number of patients, suggests that this is not necessarily the case in hematological patients. In fact, treatment with anti-CD20 antibodies was associated with preservation of bone mass in patients with follicular lymphoma receiving rituximab maintenance (Figure 2).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study describes the effect of anti-CD20 antibody treatment on bone mass in hematological patients as well as in mice. Despite previous studies suggesting that administration of anti-CD20 antibodies to SLE and RA patients may lead to bone loss (8,9), our data, albeit in a limited number of patients, suggests that this is not necessarily the case in hematological patients. In fact, treatment with anti-CD20 antibodies was associated with preservation of bone mass in patients with follicular lymphoma receiving rituximab maintenance (Figure 2).…”
Section: Discussioncontrasting
confidence: 99%
“…Another study suggested that treatment with rituximab reduced osteoclast activity as assessed by serum markers of bone resorption (7), and a recent study, also in RA patients (8), demonstrated a significant reduction in the femoral BMD with no effect in the spine. A similar effect was found in patients with systemic lupus erythematosus (female patients only), especially in those who attained a good clinical response to the treatment (9). B lymphocytes can regulate bone metabolism via their ability to secrete receptor activator for nuclear factor κ B ligand (RANKL) and osteoprotegerin (OPG) (3,10,11).…”
Section: Introductionmentioning
confidence: 60%
“…17 In pre-menopausal Mexican women with SLE, chronic disease damage, low body mass index, and cumulative corticosteroid dose were found to be risk factors for low BMD. 18 On the other hand, Bhattoa et al found that bone mass in men with SLE was not decreased despite having undergone corticosteroid therapy, and biochemical markers of bone turnover were within the reference range. 12 In accordance with the study of Bhattoa et al our present comparison of PINP with respect to age and glucocorticoid use within previous 6 months did not reveal any significant difference in female patients.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study by Mendoza Pinto et al conducted on 30 patients with SLE found that a oneyear course of treatment with rituximab, surprisingly, resulted in lower BMD at both femoral neck and lumbar spine, compared with patients without such therapy. 18 However, PINP and CTX analyses were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…17 Em mulheres mexicanas na pré-menopausa com lúpus eritematoso sistêmico, o dano crônico da doença, o baixo índice de massa corporal e a dose cumulativa de corticosteroide foram considerados fatores de risco para a baixa densidade mineral óssea. 18 Por outro lado, Bhotta et al descobriram que a massa óssea em homens com LES não diminuiu, apesar de terem sido submetidos a tratamento com corticosteroides, e os marcadores bioquímicos de remodelação óssea estavam dentro do intervalo de referência. 12 Este estudo tem algumas limitaç ões que devem ser enfatizadas.…”
Section: Tabela 2 -Correlações Entre Os Mro Hpt 25(oh)d Anticorposunclassified